Light‐Induced Refractive Index Modulation in Photoactive Liquid‐Crystalline Elastomers. Issue 23 (7th October 2013) - Tašič, Blaž; Li, Wei; Sánchez‐Ferrer, Antoni; Čopič, Martin; Drevenšek‐Olenik, Irena
<x xml:space="preserve">Abstract</x> A comparative study of UV‐irradiation‐induced refractive index modulation in two analogous monodomain nematic side‐chain liquid‐crystalline elastomer materials is conveyed. In one of them, mesogenic azobenzene derivatives are incorporated as pendant co‐monomers, and in the other as crosslinking units. The dependence of the optical diffraction properties on the polarization state of the probe beam reveals that diffraction is predominantly of a bulk origin for both materials. For prolonged UV exposures, the material with pendant azobenzene derivatives exhibits practically constant diffraction properties, while the material with cross‐linking azobenzene units shows a profound decrease of diffraction efficiency with increasing exposure time. The difference is attributed to photoinduced alignment of the azobenzene molecules, which is much stronger in the material with the crosslinking azobenzene units. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>